2021
DOI: 10.1111/ajt.16291
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells improve corneal graft survival through suppressing angiogenesis and lymphangiogenesis

Abstract: Myeloid‐derived suppressor cells (MDSC) are one of the major negative regulators of immune responses during many pathological conditions such as cancer and transplantation. Emerging evidence indicates that MDSC also contribute to tumor progression through their pro‐angiogenic activity in addition to immunosuppressive function. However, virtually nothing is known about the role of MDSC in the regulation of neovascularization after transplantation. Here we showed that antibody‐mediated depletion of MDSC in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Human umbilical cord mesenchymal stem cells (Huc-MSCs), which are widely used in NOD mice, can inhibit the differentiation of MDSC by secreting the soluble factors COX2/PGE2 and IFN-β and enhance their inhibitory ability on immune cells so as to achieve effective therapeutic effects against diabetes ( Qi et al, 2020 ). Based on the aforementioned findings, the metastasis of MDSC, f-MDSC, or the transfer of Huc-MSCs may possess the enhanced inhibitory ability on immunity and demonstrate the therapeutic effect on diabetic mice ( Yin et al, 2010 ; Xia et al, 2011 ; Torbica et al, 2019 ; Ren et al, 2021 ). MDSC-related stem cells also may be a promising treatment for diabetes.…”
Section: Mdsc Is a Candidate Target For The Treatment Of Diabetesmentioning
confidence: 99%
“…Human umbilical cord mesenchymal stem cells (Huc-MSCs), which are widely used in NOD mice, can inhibit the differentiation of MDSC by secreting the soluble factors COX2/PGE2 and IFN-β and enhance their inhibitory ability on immune cells so as to achieve effective therapeutic effects against diabetes ( Qi et al, 2020 ). Based on the aforementioned findings, the metastasis of MDSC, f-MDSC, or the transfer of Huc-MSCs may possess the enhanced inhibitory ability on immunity and demonstrate the therapeutic effect on diabetic mice ( Yin et al, 2010 ; Xia et al, 2011 ; Torbica et al, 2019 ; Ren et al, 2021 ). MDSC-related stem cells also may be a promising treatment for diabetes.…”
Section: Mdsc Is a Candidate Target For The Treatment Of Diabetesmentioning
confidence: 99%
“…The ex vivo – induced BM-MDSCs (1 × 10 6 cells) were suspended in 10 µL PBS and injected subconjunctivally into allograft recipients using a 33-gauge metal needle and 1-mL syringe (M. S. Surgical, Kalol, India) immediately after corneal transplantation according to previous studies. 19 , 25 , 26 The control mice received a PBS injection.…”
Section: Methodsmentioning
confidence: 99%
“… 18 In mice corneal transplantation, MDSCs prompted effective results. For example, Ren et al 19 reported that these cell improved graft survival through suppressing angiogenesis and lymphangiogenesis. Therefore the application of ex vivo – induced bone marrow MDSCs (BM-MDSCs) is promising for high-risk corneal transplantation in a local inflammatory environment as a potential approach for preventing graft rejection.…”
mentioning
confidence: 99%
“…Photos were automatically taken to reconstruct the entire image of the cornea. ImageJ software was then used (NIH, Bethesda, Maryland, United States) to outline the innermost lymph nodes of the limbus to calculate the total area of the cornea, and the area of the newborn lymphatic vessels in each mouse were subsequently calculated ( Ren et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%